(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the ocular tolerability of topical drug treatments of brimonide tartrate-timolol maleate, dorzolamid hydrochloride-timolol maleate and latanoprost-timolol maleate in patients with primary open angle glaucoma.